Dynamics of Postcoloniality in African Literature - Dhobi, Saleem (Cognition, 2021)
This paper examines postcolonialism by analyzing Chimamanda Adichie’s Half of a Yellow Sun. The research shows postcolonialism a set of theories in philosophy and different approaches to literary analysis concerned with literature written in English in countries. Indeed, postcolonial theorists inspect what happens when two cultures clash and one of them, with its accessory ideology, empowers and deems itself superior to the other. The paper explores how different dynamics of colonialism started to disappear by the early twentieth century. Political, social, economic, and ideological domination of England began to disappear, and the very process can be termed as decolonization. The article sheds light on the literature of Nigeria, a colonized country. After Nigeria became independent from the British colonization, the Biafra war began. Consequently, a great crack at the ethnic level took place in Nigeria. The paper investigates the ethnic conflict as portrayed in the novel. The novel embodies characters of both colonizing and colonized notions to reveal how the racial conflict retains in society. The article demonstrates the theoretical perspective of Homi Bhabha who questions the practice of generalizing and essentializing third world countries with homogeneity. Overall, the paper finds that education is the weapon for the colonized to fight back against the colonizers.